2013
DOI: 10.4172/2157-7609.1000153
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia as a Risk Factor of Ischemic Stroke

Abstract: Diabetes is considered a major risk factor for stroke and is associated with worsened stroke outcomes. Here, we discuss and summarize the mechanisms that have been associated with the increased risk of stroke due to the hyperglycemia in diabetes mellitus. In diabetic stroke models, hyperglycemia exaggerates the following damaging processes: acidosis, accumulation of reactive oxygen species/reactive nitrogen, inflammation and mitochondrial dysfunction. Understanding the mechanism of diabetes acting as a stroke … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 74 publications
1
9
0
2
Order By: Relevance
“…These results suggest that diabetic hyperglycemia aggravates brain injury induced by ischemia/reperfusion. The mechanisms of hyperglycemia-aggravated cerebral ischemia/reperfusion injury are poorly understood, and interventions for hyperglycemia-aggravated ischemic brain injury have made little progress 11 , 13 . Therefore, future studies are needed to explore the molecular mechanisms of hyperglycemia-aggravated cerebral ischemia/reperfusion injury and potential effective drugs for treating this disease 11 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that diabetic hyperglycemia aggravates brain injury induced by ischemia/reperfusion. The mechanisms of hyperglycemia-aggravated cerebral ischemia/reperfusion injury are poorly understood, and interventions for hyperglycemia-aggravated ischemic brain injury have made little progress 11 , 13 . Therefore, future studies are needed to explore the molecular mechanisms of hyperglycemia-aggravated cerebral ischemia/reperfusion injury and potential effective drugs for treating this disease 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Several animal models have confirmed that hyperglycemia increases cerebral infarct volume and cerebral hemorrhage, leading to a poorer prognosis 10 . However, the mechanisms of hyperglycemia-exacerbated cerebral ischemia/reperfusion damage are still not fully understood and there is no appropriate therapeutic approach to prevent or control the hyperglycemia-enhanced ischemic brain damage 11 . It has been reported that hyperglycemia increases neuronal death through activation of mitochondria-initiated apoptotic pathways 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Whether or not tight control of blood sugar on patients with diabetes reduces stroke risk is, however, uncertain [24] . Patients with diabetes are two to three times more likely to have ischemic stroke when compared with nondiabetic individuals [28] . Diabetes mellitus was associated with 26.25% of ischemic stroke [29] .…”
Section: Alemayehu and Birhanesilasiementioning
confidence: 99%
“…The pathophysiological mechanisms of hyperglycaemia induce oxidative stress; promote formation of advanced glycosylation end products 40 41 ; increase blood–brain barrier permeability and inflammatory responses 42 ; lead to accumulation of reactive oxygen species/reactive nitrogen, inflammation and mitochondrial dysfunction 43 ; lead to cellular dysfunction; damage vascular tissue; inhibit endogenous vascular protective factors; alter vascular homeostasis 44 ; raise levels of reactive oxygen species and advanced glycation end products; decrease levels of mitochondrial superoxide dismutase 41 and correlate with endothelial cell dysfunction and nitric oxide production. 45 All these actions contribute to accelerating the atherosclerotic process.…”
Section: Discussionmentioning
confidence: 99%